Digital intelligence as a factor in the formation of organizational digital competitiveness - Khrapach , Yana (Management and Entrepreneurship: Trends of Development, 2026)
Today, the rapid digitalization of the world economy significantly transforms the approaches to forming competitive advantages of organizations. Until recently, the key factors for the success of entrepreneurial activity were its material elements and quick access to capital, however, at the current stage of development, one of the main roles has begun to be played by the ability of an organization to work with all elements of the digital ecosystem and successfully integrate them into all processes.In this context, the issue of understanding "digital intelligence" as an essential characteristic of an organization that determines its market position in the digital competitive environment becomes particularly relevant. In scientific research, digitalization is often viewed as a technological process of implementing information systems, but insufficient attention is paid to management tools for transforming digital potential into sustainable economic effects. Thus, digital competitiveness cannot be viewed only through the prism of the existing IT infrastructure, because its provision requires a complex integration of technological, analytical, managerial and cultural forces into a single intellectual business architecture. The article proposes the author's interpretation of digital intelligence, differentiates its structural components, and presents their synergy in the process of transition from the initial digital base to the final level of digital maturity. It is demonstrated that digital intelligence is the key, transformational stage that ensures the transformation of digitalization from a point and limited in scale process into a strategic factor of development. A conceptual model of digital competitiveness formation is proposed, within which the levels of logic of transition from the creation of basic IT infrastructure to the achievement of sustainable market advantages and adaptability are shown. It is substantiated that the development of digital intelligence directly affects the growth of financial indicators of the enterprise, for example, operational efficiency, profitability and margin. It is concluded that in the conditions of the digital economy, it is the level of development of digital intelligence that determines the strategic stability and long-term competitiveness of the organization.JEL classification: O33, M15, L25.